TWO REORGANIZATIONS (1995 e 2015): OF EMPLOYMENT OF THE PAULISTA STATE NETWORK TO THE OCCUPATION OF SCHOOLS - Goulart, Debora Cristina [UNESP]; Rezende Pinto, Jose Marcelino; Camargo, Rubens Barbosa de (Univ Estadual Campinas, Fac Educacao, 2017)
This paper discusses the coincident elements between the proposals for reorganization of the public school system in Sao Paulo - the first one implemented in 1995 and the second, interrupted in 2015. There are numerous convergences that we attribute to the persistence of an educational policy based on the Principles of managerialism and productivity in the search for the rationalization of the use of educational resource The results of the study show that in the two proposals for reorganization there was negligence regarding its disclosure of studies and discussion with the population, lawsuits and subjects willing to resist popular resistance to its implementation.
Keywords: Educational reform; Regional educational bodies; Educational financial resources; Student unrest